DISINFORMASI PEMBAKARAN BENDERA KALIMAT TAUHID - Suryani, Cahya (Master of Communication Science Program, Universitas Diponegoro, 2020)
There was a burning of tauhid flag on 28 oct 2018 at kec limabngan garut. It was known as the flag of hti. This action became widely spread out through the video with many argumentation and opinion. Besides, there was false infirmation about flag burning. This study focused to give description text analysis, practical discourse analysis and socio cultural on this burning flag incident. The object of the study is the false information of tauhid flag burning. Data collection technique is documentation from turnbackhiax.id. Data analysis uses critical discourse analysis by fairclough. From the analysis, it can be concluded that there is a negative opinion construction toward muslim. Second, this negative framing has also a political situation at that time.